Relationships of the expertise level of taekwondo athletes with electromyographic, kinematic and ground reaction force performance indicators during the dollyo chagui kick - Moreira, P.; Franchini, E.; Ervilha, U.; Goethel, M.; Cardozo, A.; Gonçalves, M. (Archives of Budo, 2018)
Background and Study Aim: Taekwondo is an Olympic combat sport in which the outcome of the match is determined by points scored by kicking. By the competition rules, the roundhouse kick directed to the head (dollyo chagui) concedes the tripling of points, compared to that directed to the chest height. The aim of the study is knowledge about kinematic and neuromuscular indicators of the dollyo chagui (DC) executed by elite and subelite taekwondo athletes.